Комунікативно-прагматичний рівень мовленнєвої маніпуляції в англомовному діалогічному дискурсі: соціальна ситуація "флірт" (гендерний аспект) - Сорокіна, Ліна Євгеніївна; Sorokina, Lina Ye. (Національний університет «Одеська юридична академія», 2016)
Стаття присвячується аналізу комунікативно-прагматичного рівня мовленнєвої маніпуляції в англомовному діалогічному дискурсі. Соціальна ситуація судового допиту розглянута як типова соціальна ситуація, що провокує використання маніпулятивних стратегій і тактик. Особлива увага приділяється гендерному аспекту маніпулятивного впливу. The article deals with the analysis of the communicative and pragmatic level of verbal manipulation in English dialogical discourse. Social situation of the examination in the court is regarded as a typical social situation which provokes the usage of manipulative strategies and tactics. Dialogical manipulative situations have been revealed on the basis of their cognitive discursive and communicative pragmatic characteristics. K. Serazhym’s communicative model is taken as the basis for the simulating of the dialogical manipulative situation structure.Social situation of flirting (living environment) and social situation of the examination in the court (official environment) are typical social situations which are impossible without manipulative influence.
The Communicative and Pragmatic Level of Verbal Manipulation in English Dialogical discourse: Social Situation of Flirting (Gender Aspect)
Keywords: мовленнєва маніпуляція; маніпулятивна стратегія; гендер; соціальна ситуація флірту; verbal manipulation; manipulative strategy; gender; social situation of flirting